HE STEALS… BUT HE GETS THINGS DONE - THE PRAGMATISM OF CORRUPTION AND THE CORRUPTION OF PRAGMATISM - Sime-Rendon, Diego (2017)
The paradoxical concept of effective corrupt leadership (ECL) in Peruvian politics has been described by some analysts as an scathing and evil version of pragmatism. The present paper is a reflection which aims to get acquainted with the characteristics of pragmatism and its relation with corruption in Peru. The tolerance to corruption is a praxis of excessive political pragmatism and even more: a disproportionate manner of practicing the pragmatic aspect of truth. This praxis leads to an ethnocentric and relativist concept of truth which causes scepticism towards political discourse.